Written reflection in assessment and appraisal: GP and GP trainee views. Issue 3 (4th May 2017) - Curtis, Pamela; Taylor, Gordon; Riley, Ruth; Pelly, Tom; Harris, Michael
Abstract: Background: In the UK, evidence of written reflection is part of licensing and revalidation for general practitioners (GPs). However, there is little evidence of specific benefits compared to other forms of reflective practice.Aim: To seek GPs' and general practice (GP) trainees' views on the role of written reflection in learning and assessment.Design and setting: An online survey of 1005 GPs and GP trainees (GPTs) in the UK.Method: An anonymous questionnaire containing 38 attitudinal items was administered. Descriptive statistics were used to analyse Likert scale responses, thematic analysis for free-text responses.Results: In total 544 GPs and 461 GPTs completed the survey, with 842 (83.8%) agreeing they find verbal reflection with a colleague more useful than written reflection. Three quarters disagreed that written reflection is a way of identifying poorly performing GPs. Over 70% of respondents stated that summative, written reflection is a time-consuming, box-ticking exercise which distracts from other learning. They question its validity as part of assessment and state that its use may contribute to current difficulties with recruitment and retention to GP.Conclusions: For many GPs, written reflection is an onerous process rather than beneficial to their learning, indicating its continued use in assessment needs to be critically examined.